A CRET‐Based Multicolor Sensing Nanoplatform for Simultaneously and Sensitively Visualizing Multiple Circulating MicroRNAs. Issue 3 (7th June 2021) - Xu, Jie; Shi, Lin; Wang, Han; Li, Tao
Abstract: Circulating microRNA (miRNAs) have been proven as potential biomarkers for disease diagnosis. Herein, this work reports the design of a chemiluminescence resonance energy transfer (CRET) based multicolor sensing nanoplatform with a portable smartphone as mini‐detector for simultaneous and sensitive analysis of multiple circulating miRNAs. Universal multicomponent nucleic acid enzyme functionalized gold nanoparticle (MNAzyme@AuNP) nanoprobes activated by the addition of different target miRNAs were constructed. As a result, spherical nucleic acid enzyme (SNAzyme) with high catalytic activity for the luminol‐H2 O2 chemiluminescence or CRET reaction was produced. It enables the construction of a multicolor sensing nanoplatform for simultaneously visualizing multiple miRNAs based on chemiluminescence imaging arrays (CLIA). In this way, acute myocardial infarction (AMI) related biomarkers, miR‐133a and miR‐499, were detected with high sensitivity and selectivity in human serum. Abstract : A CRET‐based multicolor smartphone sensing nanoplatform integrating chemiluminescence (CL) imaging arrays for simultaneous and sensitive detection of multiple miRNAs has been constructed. SNAzyme with high catalytic activity for CL and chemiluminescence resonance energy transfer (CRET) reactions was produced in the presence of target miRNAs. The nanoplatform can simultaneously visualize multiple miRNAs related to acute myocardial infarction with high sensitivity and selectivity, and directly detect endogenous miRNAs in human serum.